2016
DOI: 10.1016/j.foodpol.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation formats and the WTA/WTP gap: A study of climate neutral foods

Abstract: We conduct a field valuation experiment where we vary the valuation method (contingent valuation vs. inferred valuation) as well as the payment format (dichotomous choice vs. payment card). Willingness-to-accept and willingness-to-pay valuations are elicited in a within-subjects design for foods with climate neutral labels. We find a similar gap for valuations elicited with the contingent or the inferred valuation method. However, we also find that the gap can be muted by using a payment card elicitation forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…In our opinion, this represents a comprehensive research on sustainable food purchase behaviour because it eliminates social desirability bias (Drichoutis et al, 2016) and hypocrisy (Kaiser and Byrka, 2015). Hence, the first objective of the study is to draw on Campbell's paradigm to develop a sustainable product purchase behaviour model by conceptualising and measuring behavioural difficulties in terms of Past Purchase, Premium Pricing, and Product Availability and Product Variety barriers.…”
mentioning
confidence: 99%
“…In our opinion, this represents a comprehensive research on sustainable food purchase behaviour because it eliminates social desirability bias (Drichoutis et al, 2016) and hypocrisy (Kaiser and Byrka, 2015). Hence, the first objective of the study is to draw on Campbell's paradigm to develop a sustainable product purchase behaviour model by conceptualising and measuring behavioural difficulties in terms of Past Purchase, Premium Pricing, and Product Availability and Product Variety barriers.…”
mentioning
confidence: 99%
“…Regarding the methodologies, the literature review revealed that WTP for low CF products was primarily estimated by hypothetical choice experiments. In only seven studies non-hypothetical methods were used, namely, experimental auctions in four cases (e.g., Chen, Zhang, Huang, & Zheng, 2017) and a real choice experiment in three cases (e.g., Drichoutis, Lusk, & Pappa, 2016;Drichoutis, Vassilopoulos, Lusk, & Nayga, 2017).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…Those changes let emerge the behavior of the respondent that gives extreme importance to the specific characteristic, or belong to higher income The WTP individual amount has been modeled as dependent on the explanatory independent variables listed in Table 1 and an interval regression model has been estimated to investigate the determinants of consumers' WTP for products with lower CF. The interval regression model was chosen because, like in other studies on this topic (Drichoutis et al, 2016(Drichoutis et al, , 2017, the estimates are easier to interpret and the variance of WTP is directly estimated (Hanemann & Kanninen, 2001). Table 2 summarizes the model estimates.…”
Section: A Pilot Online Survey In Italymentioning
confidence: 99%
“…Mehrere empirische Studien kommen zu dem Schluss, dass die IVM die verzerrenden Effekte von moralischer Genugtuung bzw. von Warm Glow auf bekundete Zahlungsbereitschaften verringert (Lusk/Norwood, 2009a, b;Stachtiaris et al, 2013;Yadav et al, 2013;Drichoutis et al, 2016Drichoutis et al, , 2017. Allerdings lassen auch einige Studien Zweifel aufkommen, ob die mit der IVM erhobenen Werte indi-viduelle Präferenzen adäquat wiedergeben können.…”
Section: So Zeigenunclassified